Recognition of the right to participation of tribal peoples in the repatriation of Lombok treasures - Liemanto, Airin; Fadli, Moh.; Kusumadara, Afifah; Haq, Lalu Muhammad Hayyanul (Faculty of Law, University of Muhammadiyah Malang, 2024)
This research explores the absence of the peoples of customary law in returning Lombok treasures before, during, and after repatriation, while international law and law in Indonesia recognise and respect the right to self-determination and participation of the people of customary law in a cultural sector. This article employed a normative-legal method supported by conceptual and case approaches. A descriptive-prescriptive method was employed, and data were analysed using content analysis. The results show that the government faces the challenge of determining official representatives of tribal peoples. Another challenge came from inadequate infrastructure and budget. The absence of the tribal peoples has led to the failure of achieving the reconciliation of unfair history, blocked access to helping with the research on the origin of the objects of cultural heritage, reinforced the content of agreements and cooperation of repatriation, and reintegrated the missing objects into their cultural context. This gap can be solved with two strategies reinforcing the role and participation of the tribal peoples in the repatriation process, namely by setting up the legal framework for the repatriation of cultural heritage objects and strengthening the involvement and legal standing of the tribal peoples. Through the study of Lombok treasures, this research contributes a valuable lesson and awareness, indicating that the State should recognise the right to participation of the peoples of customary law in an attempt to repatriate other objects of cultural heritage in the time to come.